Pakistan at the Crossroads : Domestic Dynamics and External Pressures - Edited by Jaffrelot, Christophe (USA Penguin Books, 2017)
Top international scholars assess Pakistan's politics and economics and the challenges faced by its civil and military regimes. Contributors examine the state's handling of internal threats, tensions among political parties, law-enforcement reform, the rise of border conflicts, financial entanglements with foreign powers, and diplomatic relations
Include Notes and Index
Keywords: Pakistan -- Diplomatic relations -- Politics and government